MARGINS OF THE NATION-STATE DISCOURSE: DIASPORIC EXPERIENCES - Lukšaitė, Eva (Politologija, 2015)
The article explores how ethnic identification and relation with homeland as well as host country changes between two generations of diasporic community. The article is based on an exploratory interpretative qualitative research – a case study of Armenian community residing in Lithuania and maintaining relations with their homeland and Armenians in other countries. The research revealed the differences of ethnic identification and diasporic experiences between generations. The first generation has chosen the strategy of integration as a way of living in the new environment: both devotion to Lithuania and preservation of ethnic identity. At the same time three different strategies of the second generation were noticed and three types of individuals were abstracted: consistent – who applies inborn principles of Armenian behaviour unambiguously and consistently; harmonious – who learns to be Armenian in his leisure time and tries to combine his Armenian and Lithuanian identities; and pragmatic – who applies ethnic principles in the situations when it is needed to play a social role.As a matter of the relation to homeland, the first generation seeks to maintain a “primordial” relation and the second – makes every effort to discover their own homeland. Individuals of both generations feel as observers, unable to escape the homeland created in Lithuania and to enter the life of the distant homeland. As far as the relation to a host country is concerned, the first generation has chosen a devotion and obligation to Lithuania and at the same time their relation is misunderstood by their offspring who see Lithuania as a temporal location.To generalize the research findings, socially and culturally integrated individuals of the second generation see their relation to undiscovered imagined homeland as more important than the relation to the country they live in. This relation is an expression of a need to consolidate their ethnic identity which serves as a basis for exceptionality and individuality. On the contrary, the first generation makes more effort to create positive relation to host society and country instead of maintaining “primordial” relation to the homeland. They use ethnic principles as a background for social reality construction and thus express a passive relation to the country of origin.